2015
DOI: 10.3109/09513590.2015.1017811
|View full text |Cite
|
Sign up to set email alerts
|

Eventual proapoptotic or anti-apoptotic impact of aberrantly expressed Cx43 and Cx26 can depend on ER-alpha overexpression in human endometrioid adenocarcinoma

Abstract: Estrogen receptor (ER) and progesterone receptor (PgR) accumulations lead to impairment of gap junctional intercellular communication in endometrial cancer. The task of this study was to explore relationships of Cx26 and Cx43 with anti-apoptotic protein Bcl-xL and proapoptotic agent Bak in ER-alpha and PgR negative or variably positive endometrioid adenocarcinomas. Cx26, Cx43, Bak, Bcl-xL, PgR and ER-alpha were detected in 78 endometrioid adenocarcinomas with immunohistochemistry. There was a remarkable cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Multiples studies have revealed that, in breast cancer patients, the expression of connexin proteins is correlated with clinicopathological biomarkers, including estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2), which are normally used to predict the response of mammary cancer patients to therapy (33,53). The Hs578T cell line used in the current study is a type of triple-negative breast cancer (TNBC), while the MCF-7 cell line is non-TNBC (ER+ and PR+) (54,55).…”
Section: A B Discussionmentioning
confidence: 99%
“…Multiples studies have revealed that, in breast cancer patients, the expression of connexin proteins is correlated with clinicopathological biomarkers, including estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2), which are normally used to predict the response of mammary cancer patients to therapy (33,53). The Hs578T cell line used in the current study is a type of triple-negative breast cancer (TNBC), while the MCF-7 cell line is non-TNBC (ER+ and PR+) (54,55).…”
Section: A B Discussionmentioning
confidence: 99%
“…Without E2, control cells become stressed with increasing confluence and upregulate genes associated with hypoxia ( Ptgis , Cryab [ 24 ]), cell death ( Casp1 , Fas [ 25 ]), and inflammatory responses involving immune cell recruitment through the TNF signalling pathway ( Ccl2 , Icam1 ) [ 26 , 27 ]. E2-treated cells appear to overcome hypoxia via up-regulation of E2-responsive Hif1a [ 28 ] and Connexin 43 ( Gja1 ) [ 29 , 30 ]. Inflammatory immunogenic signals were suppressed in E2-treated cells, suggesting that E2 may contribute to an immune-restricted microenvironment, allowing pre-neoplastic lesions to develop and evade immune surveillance [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that ERα may enhance the interaction between STAT3 and the apoptosis regulator BCL-extra large, which is crucial for the development of endometrioid adenocarcinoma (112). Furthermore, ERα expression has been indicated to influence the pro-apoptotic or anti-apoptotic effects of abnormally expressed Cx43 and Cx26 in EC (113). Regarding drug resistance, Abe et al (114) found that ERα upregulates the expression of BCL2-associated athanogene 3 (BAG3) in EC cells, inhibits the expression of miR-29b, and increases the expression of Mcl-1, which is a downstream mediator of BAG3.…”
Section: Downstream Of Erαmentioning
confidence: 99%